Systematic review and meta-analysis of two decades of reported outcomes for robotic coronary artery bypass grafting - Hwang, Bridget; Ren, Justin; Wang, Katherine; Williams, Michael L.; Yan, Tristan D. (Annals of Cardiothoracic Surgery, 2024)
Background: Despite the well-documented safety and feasibility of robotic coronary artery bypass grafting (CABG), widespread adoption of this approach remains limited by its steep learning curve, high procedural costs and paucity of data on longer-term efficacy. This current meta-analysis aims to provide a systematic overview of the outcomes of robot-assisted CABG, with a focus on long term graft patency and freedom from major adverse cardiac and cerebrovascular events (MACCE). Methods: A systematic literature search of three electronic databases was conducted for studies reporting outcomes of robotic-assisted CABG, and were grouped based on whether patients underwent robot-assisted minimally invasive direct coronary artery bypass (RA-MIDCAB), totally endoscopic coronary artery bypass (TECAB) or were mixed. Perioperative and mid-to-long term results from included studies were pooled using meta-analysis of proportion or means in a random effects model. Results: In the quantitative analysis, thirty-nine eligible studies included 6,152 patients who underwent RA-MIDCAB, 1,729 patients who underwent TECAB and 21,642 patients who underwent either form of robot-assisted CABG. A high level of heterogeneity was observed amongst baseline characteristics. Perioperative mortality and complication rates were low. Conversion rate to full sternotomy overall was less than 3.2% [95% confidence interval (CI): 2.1–5.2%, I2=39%]. At a mean follow-up duration of 5.2 years, overall graft patency was 96% for both RA-MIDCAB and TECAB, and freedom from major adverse cardiac events (MACE) or MACCE was 83.2% (95% CI: 72.0–90.4%; I2=90%) for RA-MIDCAB and 91.6% (95% CI: 86.6–94.9%; I2=76%) for TECAB. Conclusions: Robot-assisted CABG is observed to have acceptable perioperative and mid-to-long term outcomes with promising overall graft patency.